Música e diversidade em festas e folias do Divino de Goiás: Crixás, Pirenópolis e Colinas do Sul - Clímaco, Luiz Fernando Araújo (2017)
The present work addresses a variety of rhythms and music genres that are presented during the traditional festivals of “Folias do Divino Espírito Santo” in the state of Goiás – Brazil, particularly in the towns of Crixás, Pirenópolis and Colinas do Sul, where the field research took place. Based on a comparative study between the program of each one of the events and the cultural expressions present in it, we tried to understand their particular features as well as the common points in them. The aim of the work was to identify different music styles, investigating their possible origins and the historic processes they went through in each one of these places - according to their geographical location in the state region and the time of their foundation.